(untitled) (Journal of the College of Education for Women, 2019)
The marshes form large areas in southern Iraq, which are large water bodies, covered by reeds and papyrus plants. The marshes are characterized by distinctive physical elements, which have given them a unique and unique identity that can be clearly distinguished by the physical pattern. The physical environment derives its identity through a group Of inputs that interact with each other and represent both cultural and social inputs of the most important inputs that affect the formation of identity, and in the physical environment of the Marshlands many of the symbols that are associated with the collective memory of individuals, these symbols have value in the community Thus, the preservation of these symbols and inherited from one generation to another leads to the achievement of continuous physical identity through time. environment of the marshes